2012
DOI: 10.1152/jn.01089.2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the behavioral goal and environmental obstacles on rapid feedback responses

Abstract: The motor system must consider a variety of environmental factors when executing voluntary motor actions, such as the shape of the goal or the possible presence of intervening obstacles. It remains unknown whether rapid feedback responses to mechanical perturbations also consider these factors. Our first experiment quantified how feedback corrections were altered by target shape, which was either a circular dot or a bar. Unperturbed movements to each target were qualitatively similar on average but with greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
211
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(255 citation statements)
references
References 81 publications
28
211
4
Order By: Relevance
“…If the hand's position is perturbed mechanically, the hand position as estimated from kinaesthetic information changes. In that case too, the (fast) responses are timedependent, with early adjustments to mechanical perturbations being stereotyped and less tailored to task demands than later ones (Gielen et al, 1988;Smeets et al, 1995;Mutha et al, 2008;Nashed et al, 2012;Pruszynski & Scott, 2012;Nashed et al, 2014). The control strategy described in this section is consistent with a large range of experimental results, the most important being that adjustments to ongoing movements are faster than initiating new movements.…”
Section: Control Strategysupporting
confidence: 67%
“…If the hand's position is perturbed mechanically, the hand position as estimated from kinaesthetic information changes. In that case too, the (fast) responses are timedependent, with early adjustments to mechanical perturbations being stereotyped and less tailored to task demands than later ones (Gielen et al, 1988;Smeets et al, 1995;Mutha et al, 2008;Nashed et al, 2012;Pruszynski & Scott, 2012;Nashed et al, 2014). The control strategy described in this section is consistent with a large range of experimental results, the most important being that adjustments to ongoing movements are faster than initiating new movements.…”
Section: Control Strategysupporting
confidence: 67%
“…He found that, although the verbal instruction did not modulate the short-latency stretch response (i.e., 25-50 ms postperturbation onset), the magnitude of the long-latency stretch response was larger when participants were instructed to resist the perturbation. Since this seminal work, similar patterns of goal-dependent modulation have been shown in many muscles, including those acting at the jaw (Johansson et al 2014), shoulder (Kurtzer et al 2014;Nashed et al 2012;Omrani et al 2013;Pruszynski et al 2008), elbow (Cluff and Scott 2013;Colebatch et al 1979;Crago et al 1976;Evarts and Granit 1976;Nashed et al 2012Nashed et al , 2014Omrani et al 2013;Pruszynski et al 2008Pruszynski et al , 2011bRavichandran et al 2013;Rothwell et al 1980;Shemmell et al 2009), wrist (Calancie andBawa 1985;Jaeger et al 1982; Lee and Tatton 1982;Manning et al 2012), finger (Capaday and Stein 1987;Cole et al 1984;Marsden et al 1981), and ankle (Gottlieb and Agarwal 1979;Ludvig et al 2007). …”
mentioning
confidence: 69%
“…This position is supported by many demonstrations that muscular activity 50 -100 ms after a mechanical perturbation (i.e., the long-latency stretch response) shows a range of modulation that reflects voluntary motor control (for review see Pruszynski and Scott 2012;Shemmell et al 2010). Such modulation of the long-latency stretch response reflects sensitivity to task demands (Dietz et al 1994;Doemges andRack 1992a, 1992b;Hager-Ross et al 1996;Marsden et al 1981;Nashed et al 2012), movement decision-making processes (Nashed et al 2014;Selen et al 2012;Yang et al 2011), routing of sensory information across different muscles (Cole et al 1984;Dimitriou et al 2012;Marsden et al 1981;Mutha and Sainburg 2009;Ohki and Johansson 1999;Omrani et al 2013), as well as knowledge of the mechanical properties of the arm (Crevecoeur et al 2012;Crevecoeur and Scott 2013;Gielen et al 1988;Koshland et al 1991;Kurtzer et al 2008Kurtzer et al , 2009Kurtzer et al , 2013Kurtzer et al , 2014Pruszynski et al 2011a;Soechting and Lacquaniti 1988) and environment (Ahmadi-Pajouh et al 2012;Akazawa et al 1983;Bedingham and Tatton 1984;Cluff and Scott 2013;Dietz et al 1994;Kimura et al 2006;Krutky et al 2010;Perreault et al 2008;Pruszynski et al 2009;Shemmell et al 2009<...>…”
mentioning
confidence: 88%
“…Indeed, Nashed and colleagues found that corrective movements that arise ~50–100 ms after mid-reach perturbation of the limb differ depending on the spatial properties of the goal [20], and are flexible enough to redirect to an entirely new goal based on the estimated state of the limb [21•]. Similarly, by visually perturbing the location of the hand and target, Dimitriou and colleagues found that the strength of corrective responses is continually tuned to changing task demands [22•].…”
Section: Forward Models For Forelimb Movementmentioning
confidence: 99%